High-strength and conductive heterocyclic aramid composite fiber and preparation method thereof
By adding a single layer of graphene oxide to the heterocyclic aramid spinning liquid and heat treatment, rGO is formed, which solves the problems of uneven distribution of conductive materials and low fiber strength, and realizes high-strength and conductive heterocyclic aramid composite fiber, meeting the high-temperature and high-strength electromagnetic shielding needs.
Patent Information
- Application Number
- CN202411879704.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The conductive materials of existing conductive fibers are unevenly distributed, resulting in the conductive function being prone to failure, and the fiber strength is low, making it difficult to meet the high-strength and high-temperature electromagnetic shielding needs.
1-5% single-layer graphene oxide is added to the heterocyclic aramid spinning liquid, and evenly distributed it by stirring, wet spinning and heat treatment are carried out to form reduced graphene oxide (rGO), imparting electrical conductivity to the fibers and improving strength.
The heterocyclic aramid composite fiber with high strength and conductivity has a strength of up to 5.75GPa, a conductivity of 2.0S/m, and has better heat resistance. The conductivity and strength of the fibers have been significantly improved after heat treatment.
Smart Images

Figure CN119736732A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-performance fiber preparation, and specifically relates to a high-strength and conductive heterocyclic aramid composite fiber and a preparation method thereof. Background Art
[0002] Aramid fiber is widely used in many high-tech fields such as aerospace, military, and protection due to its excellent properties such as high strength, heat resistance, and flame retardancy. However, due to its electrical insulation properties, it cannot be used in some fields that require conductive functions, such as electromagnetic shielding. In some extreme environments, electromagnetic shielding requires materials to have high strength and high temperature resistance. When aramid fiber is modified to have a certain conductivity, it will be able to meet the needs of these fields and also expand the application range of aramid fiber. At present, the methods for modifying aramid fiber to prepare conductive aramid fiber mainly include coating the fiber surface with conductive materials (CN 116815494 B), such as graphene, carbon nanotubes, Mxene and other materials; or through the coaxial spinning method (CN 109811426 B), the core material is a conductive material, such as graphene, carbon nanotubes, etc., and the sheath is aramid, to obtain a core-sheath structure aramid composite fiber, and after heat treatment, the core material has conductivity.
[0003] However, the conductive fiber obtained by the coating method has a conductive layer on the surface of the fiber. During use, the conductive layer is easy to fall off and wear, and the conductive function is easy to fail. In addition, the process is relatively complicated, and the finished fiber needs to be coated and heat treated before it can be obtained. Especially for the tow, it is difficult to achieve uniform coating inside and outside.
[0004] When using the coaxial spinning method to prepare conductive fibers, the outer aramid fiber is easy to stretch due to the different stretchability of the inner and outer layers, while the inner conductive materials such as graphene and carbon nanotubes are difficult to stretch. Once stretched, they will break and the conductive path will be terminated. Therefore, in order to ensure conductivity, the spinning process cannot be stretched, which makes the strength of the entire fiber extremely low. The strength of para-aramid fiber produced by normal spinning process is about 3GPa, but the strength of this coaxial spinning process is only about 300MPa due to no stretching. Summary of the invention
[0005] In view of the problems of uneven distribution of conductive materials and low fiber strength in conductive fibers prepared by the prior art, the present invention proposes a high-strength and conductive heterocyclic aramid composite fiber and a preparation method thereof. The present invention adopts a method of adding a single-layer graphene oxide (GO) with a size of 2-5um and accounting for 1-5% of the mass fraction of heterocyclic aramid to the heterocyclic aramid spinning solution, and obtains a heterocyclic aramid spinning solution with uniform distribution of GO by simple stirring. After the spinning solution is degassed, wet spinning is performed. A nitrogen atmosphere is used during the heat treatment process. Through heat treatment, the graphene oxide in the fiber is reduced to reduced graphene oxide (referred to as rGO). rGO has excellent conductive properties and is evenly overlapped and distributed inside the fiber to form an electron path, thereby giving the aramid fiber conductivity.
[0006] One of the technical solutions of the present invention is to provide a method for preparing a high-strength and conductive heterocyclic aramid composite fiber, comprising the following steps: (1) A single layer of graphene oxide accounting for 1-5% of the mass fraction of heterocyclic aramid is added to a heterocyclic aramid spinning solution, and the heterocyclic aramid spinning solution in which the graphene oxide is uniformly distributed is obtained by stirring. The solvent of the spinning solution is DMAC. The proportion of GO in the spinning solution is crucial. When the proportion of GO is small, an electron path cannot be formed and conduction cannot be achieved. When the proportion of GO is high, the agglomeration of GO will cause the fiber strength to decrease seriously. The mass fraction of the heterocyclic aramid in the spinning solution is 2%-3%.
[0007] Furthermore, the size of the single-layer graphene oxide is 2-5 um.
[0008] (2) After the spinning solution is degassed, the spinneret is inserted into a coagulation bath for wet spinning. The coagulation bath is an ethanol aqueous solution with a mass fraction of 30-50% at -25-0°C, and a composite primary fiber in a gel state is obtained. The coagulation bath temperature is controlled at a relatively low temperature, especially below zero (-25-0°C), which can enhance the hydrogen bonding between aramid molecules and between aramid and GO molecules, thereby achieving a larger stretching multiple.
[0009] (3) The composite nascent fiber in a gel state enters a stretching bath for stretching; the stretching bath is deionized water at 1-25° C.; Furthermore, the stretching ratio is 2.8-3.2 times.
[0010] (4) Take a hot water bath at a temperature of 70-90°C; (5) Enter the tube furnace for two drying steps at temperatures of 80°C and 150°C respectively; (6) placing the sample in a tubular furnace and performing a heat treatment in a nitrogen atmosphere by a gradient temperature increase method, with the highest temperature being 400-500°C; the gradient temperature increase method comprises heating the sample from 25°C to a first temperature in 40 minutes, and keeping the sample at the first temperature for 60 minutes; heating the sample from the first temperature to a second temperature in 40 minutes, and keeping the sample at the second temperature for 40 minutes; heating the sample from the second temperature to a third temperature in 40 minutes, and keeping the sample at the third temperature for 30 minutes; Furthermore, the first temperature is 150°C, the second temperature is 250°C, and the third temperature is 400°C.
[0011] Furthermore, the gradient temperature increase method also includes increasing the temperature from the third temperature to the fourth temperature, which takes 30 minutes, and maintaining the temperature at the fourth temperature for 30 minutes; the fourth temperature is 500°C.
[0012] Through heat treatment, the graphene oxide in the fiber is reduced to reduced graphene oxide (rGO for short). rGO has excellent conductive properties and is evenly distributed inside the fiber to form an electron pathway.
[0013] After the nascent fibers have passed through a coagulation bath, a stretching bath, and a hot water bath, they need to undergo two drying treatments to fully remove the moisture and solvent in the fibers before carbonization. If they are directly carbonized without drying, the strength will be very poor. In addition, if they are first heat treated in an air atmosphere before carbonization and then carbonized in a nitrogen atmosphere, the fiber strength will also be very poor. A gradient heating method is used during the carbonization process, and the maximum carbonization temperature is controlled at 400-500°C. When the temperature is low, GO is insufficiently reduced and has no conductivity. When the temperature is too high, the fibers are severely damaged and the fiber strength is not high.
[0014] During the gradient heating method, the temperature is slowly raised from room temperature to 150°C. The water molecules remaining inside the fiber gradually migrate from the fiber part to the fiber surface, and then escape. Staying at 150°C for a certain period of time is to ensure that most of the water molecules are removed. The removal of water molecules is conducive to reducing the distance between fiber polymers, thus laying the foundation for further heating process to improve crystallinity.
[0015] Further slowly heating from 150℃ to 250℃, the solvent DMAC molecules inside the fiber gradually migrate from the fiber part to the fiber surface, and then escape, staying at 250℃ for a certain time to ensure that most of the DMAC molecules are removed. Since a relatively strong hydrogen bond is formed between the DMAC molecules and the aramid polymer, and the size and molecular weight of the DMCA molecule are much larger than that of the water molecule, a higher temperature is required to remove the DMAC molecules. The removal of the DMAC molecules further reduces the distance between the aramid polymers, strengthens the hydrogen bonding and other intermolecular forces between the aramid polymers, and is conducive to improving the crystallinity of the fiber when the temperature continues to rise.
[0016] Continue to heat up to 400 degrees and stay for a certain period of time. The energy provided at this temperature reaches the energy for the oxygen-containing groups on the GO molecules to detach from the GO molecules. Therefore, as the temperature rises, the oxygen-containing groups continue to detach from the GO molecules and migrate from the fiber to the surface, and then escape. In this process, GO gradually transforms into rGO, and the formation of rGO gives the aramid fiber conductivity. At the same time, at this stage, since the water molecules and DMAC molecules have been completely removed, as the temperature rises, the aramid polymer is further compressed, and the distance between the molecules is further reduced, thereby greatly improving the crystallinity in the fiber.
[0017] The temperature is further raised to 500°C to further remove the oxygen-containing groups on the GO molecules and improve the fiber crystallinity, and to repair the defects inside the rGO molecules to a certain extent, thereby improving the conductivity and strength. If the temperature is further raised to more than 500°C, it exceeds the decomposition temperature of the aramid molecules, and some aramid polymers begin to decompose, which will cause a sharp drop in fiber strength.
[0018] The second technical solution of the present invention is to provide a high-strength and conductive heterocyclic aramid composite fiber prepared by the above method. The graphene heterocyclic aramid composite fiber prepared by this method has a strength of up to 5.75GPa, an elongation at break of 3.68%, a resistivity of 0.5Ω•m, and a conductivity of 2.0S / m. And the graphene heterocyclic aramid composite fiber has better heat resistance than the pure heterocyclic aramid composite fiber. After being treated at 200℃ for 24 hours, the strength of the pure heterocyclic aramid fiber decreased from 5.31GPa to 3.02GPa, a decrease of 43%; the strength of the graphene heterocyclic aramid composite fiber decreased from 5.75GPa to 4.19GPa, a decrease of 27%.
[0019] Beneficial effects of the present invention: 1) By compounding DMAC phase small-sized single-layer graphene oxide with DMAC phase heterocyclic aramid, a spinning solution with uniform GO distribution can be obtained by simple stirring.
[0020] 2) High-strength conductive aramid fiber can be produced through ordinary wet spinning process, which is easy to realize industrialization.
[0021] 3) After proper drying and gradient temperature heat treatment, the addition of GO improves the fiber strength to a certain extent and gives the fiber conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the process of the present invention.
[0023] Figure 2 The scanning electron microscope images of Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0024] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.
[0025] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.
[0026] The embodiments of the present invention are further described below with reference to a plurality of embodiments.
[0027] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0028] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0029] Example 1 A single layer of graphene oxide (GO) with a size of 2um and a mass fraction of 1% of heterocyclic aramid was added to the DMAC heterocyclic aramid spinning solution as the solvent, and a spinning solution with a mass fraction of 2% of heterocyclic aramid with GO uniformly distributed was obtained by stirring. The nascent fiber enters a coagulation bath at a temperature of -25°C, and the coagulation bath composition is a 30% ethanol aqueous solution. After that, the fiber in the gel state enters a water stretching bath at a temperature of 1°C, with a stretching ratio of 3.2 times, and then enters a hot water wash at a temperature of 90°C for water washing. After water washing, it enters a tubular furnace for two continuous dryings at temperatures of 80°C and 150°C, respectively. Then put it into a tubular furnace for carbonization under nitrogen atmosphere, and use the gradient heating method to heat from 25℃ to 150℃, which takes 40 minutes, and keeps at 150℃ for 60 minutes; from 150℃ to 250℃, it takes 40 minutes, and keeps at 250℃ for 40 minutes; from 250℃ to 400℃, it takes 40 minutes, and keeps at 400℃ for 30 minutes; from 400℃ to 500℃, it takes 30 minutes, and keeps at 500℃ for 30 minutes, and then naturally cools to 25 degrees. The strength of the prepared graphene heterocyclic aramid composite fiber is 5.75GPa, the elongation at break is 3.68%, the resistivity is 0.5Ω•m, and the conductivity is 2.0S / m. And the graphene heterocyclic aramid composite fiber has better heat resistance than the pure heterocyclic aramid composite fiber. After treatment at 200°C for 24 hours, the strength of pure heterocyclic aramid fiber decreased from 5.3 GPa to 3.02 GPa, a decrease of 43%; the strength of graphene heterocyclic aramid composite fiber decreased from 5.75 GPa to 4.19 GPa, a decrease of 27%.
[0030] Example 2 A single layer of graphene oxide (hereinafter referred to as GO) with a size of 5um and a mass fraction of 5% of heterocyclic aramid was added to the DMAC heterocyclic aramid spinning solution as the solvent, and a spinning solution with a mass fraction of 3% of heterocyclic aramid in which GO was uniformly distributed was obtained by stirring. After degassing, the spinning solution was wet-spun. The spinning process is that the primary fiber enters a coagulation bath at a temperature of -25°C, and the coagulation bath composition is 30% ethanol aqueous solution. After that, the fiber in the gel state enters a water stretching bath at a temperature of 1°C, with a stretching ratio of 2.8 times, and then enters a hot water wash at a temperature of 90°C for water washing. After water washing, it enters a tubular furnace for two continuous dryings at temperatures of 80°C and 150°C, respectively. Then put it into a tubular furnace for carbonization under nitrogen atmosphere, and use the gradient heating method to heat from 25℃ to 150℃, which takes 40 minutes, and keeps at 150℃ for 60 minutes; from 150℃ to 250℃, which takes 40 minutes, and keeps at 250℃ for 40 minutes; from 250℃ to 400℃, which takes 40 minutes, and keeps at 400℃ for 30 minutes; from 400℃ to 500℃, which takes 30 minutes, and keeps at 500℃ for 30 minutes, and then naturally cools to 25℃. The obtained graphene heterocyclic aramid composite fiber has a strength of 3.1GPa, an elongation at break of 2.68%, a resistivity of 0.1Ω•m, and a conductivity of 14.4S / m.
[0031] Example 3 A single layer of graphene oxide (hereinafter referred to as GO) with a size of 2um and a mass fraction of 1% of heterocyclic aramid was added to the DMAC heterocyclic aramid spinning solution as the solvent, and a spinning solution with a mass fraction of 2% of heterocyclic aramid in which GO was uniformly distributed was obtained by stirring. After degassing, the spinning solution was wet-spun. The spinning process is that the primary fiber enters a coagulation bath with a temperature of 0°C, and the coagulation bath composition is 30% ethanol aqueous solution. After that, the fiber in the gel state enters a water stretching bath with a temperature of 1°C and a stretching ratio of 2.8 times, and then enters a hot water wash at a temperature of 70°C for water washing. After water washing, it enters a tubular furnace for two continuous dryings at temperatures of 80°C and 150°C, respectively. Then it was placed in a tubular furnace for carbonization under nitrogen atmosphere, and the temperature was increased by gradient heating method, from 25℃ to 150℃, which took 40 minutes, and kept at 150℃ for 60 minutes; from 150℃ to 250℃, which took 40 minutes, and kept at 250℃ for 40 minutes; from 250℃ to 400℃, which took 40 minutes, and kept at 400℃ for 30 minutes, and then naturally cooled to 25℃. The obtained graphene heterocyclic aramid composite fiber has a strength of 4.5GPa, an elongation at break of 3.21%, a resistivity of 15Ω•m, and a conductivity of 0.2S / m.
[0032] Example 4 A single layer of graphene oxide (hereinafter referred to as GO) with a size of 2um and a mass fraction of 1% of heterocyclic aramid was added to the DMAC heterocyclic aramid spinning solution as the solvent, and a spinning solution with a mass fraction of 2% of heterocyclic aramid in which GO was uniformly distributed was obtained by stirring. After degassing, the spinning solution was wet-spun. The spinning process is that the primary fiber enters a coagulation bath at a temperature of -25°C, and the coagulation bath composition is 50% ethanol aqueous solution. After that, the fiber in the gel state enters a water stretching bath at a temperature of 25°C, with a stretching ratio of 3.0 times, and then enters a hot water wash at a temperature of 90°C for water washing. After water washing, it enters a tubular furnace for two continuous dryings at temperatures of 80°C and 150°C, respectively. Then put it into a tubular furnace for carbonization under nitrogen atmosphere, and use the gradient heating method to heat from 25℃ to 150℃, which takes 40 minutes, and keeps at 150℃ for 60 minutes; from 150℃ to 250℃, which takes 40 minutes, and keeps at 250℃ for 40 minutes; from 250℃ to 400℃, which takes 40 minutes, and keeps at 400℃ for 30 minutes; from 400℃ to 500℃, which takes 30 minutes, and keeps at 500℃ for 20 minutes, and then naturally cools to 25℃. The obtained graphene heterocyclic aramid composite fiber has a strength of 4.9GPa, an elongation at break of 3.99%, a resistivity of 0.8Ω•m, and a conductivity of 1.5S / m.
[0033] Comparative Example 1 DMAC was added to the spinning solution of heterocyclic aramid fiber whose solvent was DMAC, and a spinning solution with a mass fraction of heterocyclic aramid fiber of 2% was obtained by stirring. After degassing, the spinning solution was wet-spun. The spinning process was that the nascent fiber entered a coagulation bath at a temperature of -25°C, and the coagulation bath composition was a 30% ethanol aqueous solution. After that, the fiber in the gel state entered a water stretching bath at a temperature of 1°C, with a stretching ratio of 3.0 times, and then entered a hot water wash at a temperature of 90°C for water washing. After water washing, it entered a tubular furnace for two continuous dryings at temperatures of 80°C and 150°C, respectively. Then put it into a tubular furnace for carbonization under nitrogen atmosphere, and use the gradient heating method to heat from 25℃ to 150℃, which takes 40 minutes, and keeps at 150℃ for 60 minutes; from 150℃ to 250℃, which takes 40 minutes, and keeps at 250℃ for 40 minutes; from 250℃ to 400℃, which takes 40 minutes, and keeps at 400℃ for 30 minutes; from 400℃ to 500℃, which takes 30 minutes, and keeps at 500℃ for 30 minutes, and then naturally cools to 25℃. The strength of the heterocyclic aramid fiber prepared by this method is 2.74GPa, the elongation at break is 2.62%, and the conductivity cannot be measured.
[0034] Comparative Example 2 A single layer of graphene oxide with a size of 2-5um and a mass fraction of 1% of heterocyclic aramid was added to the spinning solution of heterocyclic aramid with DMAC as the solvent, and a spinning solution with a mass fraction of 2% of heterocyclic aramid with uniform GO distribution was obtained by stirring. After degassing, the spinning solution was wet-spun. The spinning process is that the primary fiber enters a coagulation bath with a temperature of 25°C, and the coagulation bath composition is 30% ethanol aqueous solution. After that, the fiber in the gel state enters a water stretching bath with a temperature of 25°C and a stretching ratio of 2.6 times, and then enters a hot water wash at a temperature of 90°C for water washing. After water washing, it enters a tubular furnace for two continuous dryings at temperatures of 80°C and 150°C, respectively. Then put it into a tubular furnace for carbonization under nitrogen atmosphere, and use the gradient heating method to heat from 25℃ to 150℃, which takes 40 minutes, and keeps at 150℃ for 60 minutes; from 150℃ to 250℃, which takes 40 minutes, and keeps at 250℃ for 40 minutes; from 250℃ to 400℃, which takes 40 minutes, and keeps at 400℃ for 30 minutes; from 400℃ to 500℃, which takes 30 minutes, and keeps at 500℃ for 30 minutes, and then naturally cools to 25℃. The graphene heterocyclic aramid composite fiber prepared by this method has a strength of 2.1GPa and an elongation at break of 2.31%, and the conductivity cannot be measured.
[0035] Comparative Example 3 A single layer of graphene oxide (GO) with a size of 2-5um and a mass fraction of 1% of heterocyclic aramid was added to the DMAC heterocyclic aramid spinning solution as the solvent, and a spinning solution with a mass fraction of 2% of heterocyclic aramid in which GO was uniformly distributed was obtained by stirring. After degassing, the spinning solution was wet-spun. The spinning process is that the primary fiber enters a coagulation bath at a temperature of -25°C, and the coagulation bath composition is 30% ethanol aqueous solution. After that, the fiber in the gel state enters a water stretching bath at a temperature of 1°C, and the stretching ratio is 3.2 times, and then enters a hot water wash at a temperature of 90°C for water washing. Then put it into a tubular furnace for carbonization under nitrogen atmosphere, and use the gradient heating method to heat from 25°C to 150°C, which takes 40 minutes, and keeps at 150°C for 60 minutes; from 150°C to 250°C, which takes 40 minutes, and keeps at 250°C for 40 minutes; from 250°C to 400°C, which takes 40 minutes, and keeps at 400°C for 30 minutes; from 400°C to 500°C, which takes 30 minutes, and keeps at 500°C for 30 minutes, and then naturally cools to 25°C. The graphene heterocyclic aramid composite fiber prepared by this method has a strength of 0.92GPa and an elongation at break of 1.91%, and the conductivity cannot be measured.
[0036] Comparative Example 4 A single layer of graphene oxide (hereinafter referred to as GO) with a size of 2-5um and a mass fraction of 1% of heterocyclic aramid is added to the DMAC heterocyclic aramid spinning solution as the solvent, and a spinning solution with a mass fraction of 2% of heterocyclic aramid in which GO is uniformly distributed is obtained by stirring. After the spinning solution is degassed, wet spinning is performed. The spinning process is that the primary fiber enters a coagulation bath at a temperature of -25°C, and the coagulation bath composition is a 30% ethanol aqueous solution. After that, the fiber in the gel state enters a water stretching bath at a temperature of 1°C, with a stretching ratio of 3.2 times, and then enters a hot water wash at a temperature of 90°C for water washing. After water washing, it enters a tubular furnace for two continuous dryings at temperatures of 80°C and 150°C, respectively, and then undergoes continuous heat treatment in an air atmosphere at a heat treatment temperature of 350°C. Then put it into a tubular furnace for carbonization under nitrogen atmosphere, and use the gradient heating method to heat from 25℃ to 150℃, which takes 40 minutes, and keeps at 150℃ for 60 minutes; from 150℃ to 250℃, which takes 40 minutes, and keeps at 250℃ for 40 minutes; from 250℃ to 400℃, which takes 40 minutes, and keeps at 400℃ for 30 minutes; from 400℃ to 500℃, which takes 30 minutes, and keeps at 500℃ for 30 minutes, and then naturally cools to 25℃. The graphene heterocyclic aramid composite fiber prepared by this method has a strength of 1.86GPa and an elongation at break of 2.45%, and the conductivity cannot be measured.
[0037] Comparative Example 5 A single layer of graphene oxide (hereinafter referred to as GO) with a size of 2-5um and a mass fraction of 1% of heterocyclic aramid is added to the DMAC heterocyclic aramid spinning solution as the solvent, and a spinning solution with a mass fraction of 2% of heterocyclic aramid in which GO is uniformly distributed is obtained by stirring. After degassing, the spinning solution is wet-spun. The spinning process is that the primary fiber enters a coagulation bath at a temperature of -25°C, and the coagulation bath composition is a 30% ethanol aqueous solution. After that, the fiber in the gel state enters a water stretching bath at a temperature of 1°C, with a stretching ratio of 3.2 times, and then enters a hot water wash at a temperature of 90°C for water washing. After water washing, it enters a tubular furnace for two continuous dryings at temperatures of 80°C and 150°C, respectively. Then put it into a tubular furnace for carbonization under nitrogen atmosphere, and use the gradient heating method to heat from 25℃ to 150℃, which takes 40 minutes, and keeps at 150℃ for 60 minutes; from 150℃ to 250℃, which takes 40 minutes, and keeps at 250℃ for 40 minutes; from 250℃ to 400℃, which takes 40 minutes, and keeps at 400℃ for 30 minutes; from 400℃ to 600℃, which takes 30 minutes, and keeps at 600℃ for 30 minutes, and then naturally cools to 25℃. The graphene heterocyclic aramid composite fiber prepared by this method has a strength of 1.35GPa, an elongation at break of 2.15%, a resistivity of 0.02Ω•m, and a conductivity of 156.8S / m.
[0038] Comparative Example 6 The same as Example 1, except that the gradient heating method is not used in the tube furnace, and the temperature is directly heated to 500 degrees at a heating rate of 10°C / min and kept warm for 30 minutes. The graphene heterocyclic aramid composite fiber prepared by this method has a strength of 1.7 GPa, an elongation at break of 1.9%, a resistivity of 5Ω•m, and a conductivity of 0.2S / m.
[0039] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.
Claims
1. A method for preparing high-strength and conductive heterocyclic aramid composite fibers, characterized in that: The following steps are involved: (1) adding a single layer of graphene oxide accounting for 1-5% of the mass fraction of the heterocyclic aramid to a heterocyclic aramid spinning solution, stirring to obtain a heterocyclic aramid spinning solution in which the graphene oxide is uniformly distributed, wherein the solvent of the spinning solution is DMAC; (2) After the spinning solution is degassed, the spinneret is inserted into a coagulation bath for wet spinning. The coagulation bath is a 30-50% ethanol aqueous solution at -25-0°C to obtain a composite primary fiber in a gel state; (3) The composite nascent fiber in a gel state enters a stretching bath for stretching; the stretching bath is deionized water at 1-25° C.; (4) Take a hot water bath at a temperature of 70-90°C; (5) Enter the tube furnace for two drying steps at temperatures of 80°C and 150°C respectively; (6) placing the sample in a tubular furnace and performing heat treatment in a nitrogen atmosphere by a gradient temperature increase method, with the highest temperature being 400-500° C.; the gradient temperature increase method is to increase the temperature from 25° C. to the first temperature, which takes 40 minutes, and then keep the temperature at the first temperature for 60 minutes; It takes 40 minutes to heat up from the first temperature to the second temperature, and keep it at the second temperature for 40 minutes; it takes 40 minutes to heat up from the second temperature to the third temperature, and keep it at the third temperature for 30 minutes.
2. The preparation method according to claim 1, characterized in that: In step (6), the first temperature is 150°C, the second temperature is 250°C, and the third temperature is 400°C.
3. The preparation method according to claim 1, characterized in that: The gradient heating method in step (6) further includes heating from the third temperature to the fourth temperature, which takes 30 minutes, and maintaining the temperature at the fourth temperature for 20-30 minutes; the fourth temperature is 500°C.
4. The preparation method according to claim 1, characterized in that: The mass fraction of the heterocyclic aramid fiber in the spinning solution in step (1) is 2%-3%.
5. The preparation method according to claim 1, characterized in that: The size of the single-layer graphene oxide in step (1) is 2-5 um.
6. The preparation method according to claim 1, characterized in that: The stretching ratio in step (3) is 2.8-3.2 times.
7. A high-strength and conductive heterocyclic aramid composite fiber prepared by the preparation method as claimed in claim 1.
Citation Information
Patent Citations
A flexible conductive fiber with a core-sheath structure and its preparation method
CN109811426B
Aramid composite conductive fiber and preparation method and use thereof
CN116815494B
Preparation method of polyimide / graphene composite carbon film
CN110240150A
Preparation method of single-layer graphene oxide reinforced high-strength and high-toughness heterocyclic aramid fiber
CN117845360A